Dysregulated Cell Signaling in Pulmonary Emphysema - Lin, Chih-Ru; Bahmed, Karim; Kosmider, Beata (Frontiers in Medicine, 2022)
Pulmonary emphysema is characterized by the destruction of alveolar septa and irreversible airflow limitation. Cigarette smoking is the primary cause of this disease development. It induces oxidative stress and disturbs lung physiology and tissue homeostasis. Alveolar type II (ATII) cells have stem cell potential and can repair the denuded epithelium after injury; however, their dysfunction is evident in emphysema. There is no effective treatment available for this disease. Challenges in this field involve the large complexity of lung pathophysiological processes and gaps in our knowledge on the mechanisms of emphysema progression. It implicates dysregulation of various signaling pathways, including aberrant inflammatory and oxidative responses, defective antioxidant defense system, surfactant dysfunction, altered proteostasis, disrupted circadian rhythms, mitochondrial damage, increased cell senescence, apoptosis, and abnormal proliferation and differentiation. Also, genetic predispositions are involved. Here, we comprehensively review studies regarding dysregulated cell signaling, especially in ATII cells, and their contribution to alveolar wall destruction in emphysema. Relevant preclinical and clinical interventions are also described.